Algorithmic Bias and Ai Surveillance: A Human Rights and Legal Analysis of Women’s Digital Safety in Sri Lanka - Fernando, M.S.D. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
In an era where Artificial Intelligence (AI) increasingly shapes social, economic, and governance structures, its growing influence in Sri Lanka’s digital ecosystem has introduced both opportunities and profound risks, particularly for women navigating online spaces. While AI enhances efficiency and connectivity, it concurrently reproduces and intensifies structural gender biases through discriminatory profiling, harmful content amplification, and privacy intrusions. This study addresses the critical problem that Sri Lanka’s existing legal and policy frameworks, rooted in general cybercrime provisions and gender-neutral digital regulations, remain insufficient to safeguard women from these AI-mediated harms. The research is structured around four key objectives such as to examine how AI-driven technologies impact women’s digital safety and autonomy, to assess the adequacy of current statutory, constitutional, and policy protections, to analyse comparative regulatory models that embed transparency, accountability, and gender-responsive safeguards, and to propose viable legal and policy reforms suitable for Sri Lanka’s context. Employing a qualitative doctrinal methodology enriched by comparative legal analysis, the study critically engages with domestic legislation, international instruments such as CEDAW and the ICCPR, judicial interpretations, scholarly literature, and civil society reports. The findings reveal that Sri Lanka’s regulatory landscape is fragmented and outdated, lacking mechanisms for algorithmic accountability, bias mitigation, and platform oversight, leaving women, especially those in rural and marginalized communities, vulnerable to compounded digital harms. Comparative jurisdictions demonstrate the effectiveness of risk-based AI regulation, mandatory algorithmic impact assessments, and structured digital safety regimes. The study concludes that Sri Lanka urgently requires a comprehensive, gender-sensitive AI governance framework that strengthens privacy protections, enhances institutional capacity, and ensures meaningful accountability for AI systems, thereby securing women’s digital rights in an increasingly automated future.
Keywords: Artificial intelligence; Women’s digital rights; Gender bias; Cyberlaw; Women’s rights